Exploring basic psychological needs within and across domains of physical activity - Birgitte Westerskov Dalgas; Karsten Elmose-Østerlund; Thomas Viskum Gjelstrup Bredahl (International Journal of Qualitative Studies on Health & Well-Being, 2024)
Purpose This study explored variations in adults’ experience of satisfaction, unfulfilment and frustration of basic psychological needs within and across four domains of physical activity: Transport, household, occupation, and recreation. Methods We utilized a qualitative approach, conducting semi-structured interviews with a diverse group of 42 Danish adults. The participants ranged in age from 16 to 79 years (mean age 49 years, SD 21 years), gender (45% men, 55% women), and physical activity levels (38% low, 33% average, 29% high). Data were analysed using a thematic analysis, applying Self-Determination Theory as the guiding framework. Results In the Transport domain, while most activities were seen as utilitarian necessities, autonomy satisfaction emerged for some through control over their means of transport. In Household domain, tasks were generally viewed as obligatory; however, activities with personal significance led to autonomy satisfaction and skill development. Occupation-wise, physical activity satisfaction varied, with the nature of the job impacting feelings of autonomy and competence. For Recreation domain, personal choice dictated autonomy satisfaction, with competence and relatedness varying according to goal achievement and social interactions. Conclusion The variations in the findings across domains indicate the effectiveness of applying strategies tailored to specific domains for enhancing need satisfaction.